Why it Hurts – Save the Children Norway and the Dilemmas of 'Going Global'. Issue 1 (2nd January 2019) - Kloster, Maren Olene
Abstract: In March 2017, Save the Children International complied with the reinstated Mexico City Policy, banning US funding to foreign non-governmental organizations (NGOs) that inform about, advocate for, or provide abortion services. Several of its member organizations, among them Save the Children Norway, strongly opposed this decision, arguing that reproductive health is not solely about health but also concerns rights. This article explores how Save the Children's pragmatic choice of going global and becoming an international NGO creates various ideological dilemmas for Save the Children Norway, challenging its identity as a civil society actor. It draws on fieldwork conducted within Save the Children Norway 2014–2017, to identify some internal and ideological dilemmas faced by Save the Children Norway and staff as they try to preserve their autonomy and identity while being part of a one of the world's largest NGOs – Save the Children International.